(untitled) (Revista Argentina de Musicología, 2014)
The “spatial turn” developed in the philosophical thought of the 1970s had repercussions on the later development of disciplines studying the implications of space in the whole of human life. Based on musical and musicological knowledge, this paper approaches these concerns in order to propose a counterpoint between musical production and contemporary general theory about space. It attempts to explore the ways in which music represents space, a flexion from a predominantly visual system to one that is aural, sonic and performative. The inquiry proceeds from current conceptual frameworks about that dimension of reality, about its experience and about the records that account for it, in its various forms and origins. The unit of analysis is Argentine art music of the 20th and 21st centuries.